Tunable narrowband THz generation in orientation patterned gallium phosphide for THz anisotropy identification - McNee, I.; Tekavec, P.; Kozlov, V.; Markelz, A. G.; George, D. K.; Schunemann, P. (Nonlinear Frequency Generation and Conversion: Materials and Devices Xviii, 2019)
We demonstrate tunable narrowband THz generation by optical rectification of a femtosecond pulse in Orientation Patterned Gallium Phosphide. Center frequencies of 0.9 - 3.8 THz with average power up to 15 mu W were achieved using a 1.064 mu m fiber laser for the pump laser. Biomolecular characterization for an early application of this system is also shown in this work by anisotropic spectroscopic signature detection of molecular crystals in the THz region.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation